2003
DOI: 10.1034/j.1600-0781.2003.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of the use of a risk estimation model to assess the increased risk of non‐melanoma skin cancer among outdoor workers in Central Queensland, Australia

Abstract: The increased risk estimates did not show any significant changes for variations in occupational and recreational exposure. A maximum change of 20% was computed for 25% variation in childhood exposure, which was mainly for the APMDP with high occupational exposure levels and more than 10 years of occupational exposure. The increased risk estimates are useful to identify high risk groups at an early age and implement long-term protective measures against NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 23 publications
1
39
1
Order By: Relevance
“…Radespiel et al in a report from Germany in 2009 described that outdoor jobs and contact with sunlight are mostly accompanied by BCC, a finding in harmony with the results of the present study (6). Similarly, in another study by Vishvakarman and Wong an association between outdoor job and skin cancer was demonstrated (9). The ratio of developing BCC to SCC was 3.1 in our study which is compatible with those of others.…”
Section: Discussionsupporting
confidence: 83%
“…Radespiel et al in a report from Germany in 2009 described that outdoor jobs and contact with sunlight are mostly accompanied by BCC, a finding in harmony with the results of the present study (6). Similarly, in another study by Vishvakarman and Wong an association between outdoor job and skin cancer was demonstrated (9). The ratio of developing BCC to SCC was 3.1 in our study which is compatible with those of others.…”
Section: Discussionsupporting
confidence: 83%
“…So sunbathing at a beach for one day every year has a higher lifetime relative risk for SCC than having 40 NLO biopsies at a peak energy fluence of 500 Jm À2 in lifetime. Outdoor workers on the other hand, have an even higher relative risk for SCC ranging from 2.3-5.5, depending on outdoor profession and latitude of country [26,27]. Thus the risks for SCC from such circumstances are much higher than that from NLO imaging.…”
Section: Estimating Carcinogenic Risk Increase From Nonlinear Biopsy mentioning
confidence: 99%
“…Spending one afternoon on a beach in northern Europe increases the cumulative solar radiation re- [26], post mail delivery personnel had a relative risk for SCC as high as 5.5, while physical education teachers had a relative risk of 2.3. Another study conducted by Radespiel-Trö ger et al [27] in Germany, found the relative risk for SCC to range from 2.5-3.6 for an outdoor worker, as compared to an indoor worker.…”
Section: Relative Cancer Risk From Sun-bathing and Outdoor Professionmentioning
confidence: 99%
“…This has been accounted for in past research to determine annual exposures (28,29,30,31,32). The methodology of Vishvakarman and Wong (28) is modified for this research that assumes an annual UVE exposure is accrued by the summation of exposures received during normal working days in which the individual spends 1.5 hours traveling to, from and at work daily, and receives between 4 to 6 hours exposure during weekends and annual leave periods.…”
Section: Estimates Of Annual Uve Exposurementioning
confidence: 99%
“…By making relative comparisons, the dependence on the age of the individual can be removed (27,28). This technique was recently applied to calculate relative basal and squamous cell carcinoma risk for golfers in southern Queensland compared to office workers (10).…”
Section: Introductionmentioning
confidence: 99%